PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI SEKRETARIAT DPRK BIREUEN - Konadi, Win; Jalal, Faisal (JURNAL KEBANGSAAN, 2019)
The purpose of this study, in accordance with the formulation of the problem posed, is for 1). analyze the effect of work motivation on employee performance at the Bireuen DPRK Secretariat. 2. analyze the influence of the work environment on employee performance at the DPRK Secretariat Bireuen. And to analyze the influence of work motivation and work environment, together on the performance of employees in the DPRK Secretariat Bireuen. Based on the analysis of sample data of 30 employees of the DPRK Bireuen secretariat, from the results of the correlation analysis approach, the correlation of work motivation and work environment to the performance was 0.854, including high. So that there is 72.9% contribution to work motivation and work environment variables on employee performance. From the results of the multiple linear regression analysis approach, it was proven that work motivation had an effect on performance, and the work environment also had an effect on performance, with a regression model Y = - 7.921 + 1,182 X1 + 1,419 X2 The influence of the work environment was higher than work motivation. Keywords: Work Motivation, Work Environment, Secretariat Performance of DPRK Secretariat Bireuen.